Improve Your English Through The 21st Century Skills - Shobahul Hoir; M. Subandowo; Yoso Wiyarno (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2019)
Entering the second decade of the 21st century means that the implementation of the 21st century education pattern in Indonesia must be implemented. The Partnership (P21) for 21st Century Skill identifies four important abilities called 'Four Cs' or 4Cs, consisting of collaboration (collaboration), critical thinking (critical thinking), creativity (creativity), and communication (communication). This study aims to develop teaching material products in English through 4Cs. The procedure for developing teaching materials uses the ADDIE development model which consists of five stages, namely: analysis, design, development, implementation, and evaluation. The data collected aims to see the feasibility of the product as teaching material and field trials in the learning class. The questionnaire data came from material experts (SME), learning design experts, peers, and 30 students. This analysis technique is used to process the data obtained / collected through a questionnaire in the form of a descriptive percentage. The results of the feasibility review of the development product are as follows: 1) Expert review of English material by 90%, expert review of learning design by 90%, 2) Product testing to students and teachers through questionnaires gets a very good response. Based on the results of the product feasibility review, it can be concluded that this development product is very suitable for use in the English learning process to direct students in developing 21st century skills. Suggestions for the use of this product are that the teacher becomes a guide and motivator for students for the 21st century ability development process